Miłosierny styl życia chrześcijańskiego według papieża Franciszka - Warzeszak, Józef (Warszawskie Studia Teologiczne, 2017)
The teachings of Pope Francis described demonstrate how important it is to him to accustom Christians to a merciful lifestyle and to revive the mercy culture. If the way of the Church – as St. John Paul II taught in accordance with the Second Vatican Council – is man, then for Pope Francis, the way of the Church is a man who needs God’s mercy in the form of being preached the word of God, repentance, and absolution of sins to, in other words – a sinful and repentant man; and then a man who is poor – who needs material support, restoration of justice and dignity of God’s image, spiritual consolation, acceptance, affection and compassion. Christians are obliged to share the mercy granted by God and people with others. They are to imitate merciful Jesus, see Him in the poor and suffering, be the outstretched hands of Christ and of His merciful Mother. The Pope wishes mercy not to be merely talked about, but also to be lived by.